Short birth interval and its predictors among reproductive age women in high fertility countries in sub-Saharan Africa: a multilevel analysis of recent Demographic and Health Surveys - Tadele Biresaw Belachew; Desale Bihonegn Asmamaw; Wubshet Debebe Negash (BMC, 2023)
Abstract Background In developing countries, short birth interval is one of the major public health issues. It is one of the leading cause's adverse birth outcomes in the worldwide. Despite the fact that ending maternal and perinatal morbidity and mortality is one of the Sustainable Development Goals (SDG), the burden of the problem continues to be a huge concern in developing countries, including high fertility countries. Thus, this study aimed to determine the short birth interval and its predictors in ten high fertile sub-Saharan African countries. Methods Data for this study was obtained from the most recent Demographic and Health Surveys (DHS). A total of weighted sample of 303,979 women of childbearing age group (15- 49) who had at least two alive consecutive children was included. A multilevel mixed-effect binary logistic regression model was fitted to identify the associated factors of short birth interval. As a final step, the Adjusted Odds Ratio (AOR) was used with a confidence interval of 95% in determining statistical significance. Results Overall prevalence of short birth interval in high fertile sub Saharan Africa was 58.74% (52.32%, 65.17%).The factors significantly associated with the short birth interval were women's educational status; primary education (AOR = 0.88; 95% CI: 0.86,0 .91), secondary and higher (AOR = 0.10; 95% CI: 0.09, 0.11), working (AOR = 0.91; 95% CI: 0.88, 0 .93), classified as rich wealth index level (AOR = 0.90; 95% CI: 0.88, 0.93),having six and above ideal number of children (AOR = 2.25; 95% CI: 2.22, 2.30), preferred waiting time two years and above to give birth (AOR = 0.83; 95% CI: 0.76, 0.89), contraceptive non users (AOR = 3.01; 95% CI: 2.93, 3.07), community level education (AOR = 1.97; 95% CI: 1.54, 2.08), rural residency (AOR = 2.17; 95% CI: 2.13, 2.22), and country Chad (AOR = 1.37; 95% CI: 1.22, 1.54). Conclusion The prevalence of short birth interval in the top ten high fertile sub Saharan African countries is still optimally high. Therefore, the government of each country should work on the access to family planning and education in rural parts of the countries.